Analisis Bibliometrik Terhadap Penelitian Modal Sosial dan Ketahanan Ekonomi dalam Usaha Kecil dan Menengah (UKM) - Hawa Rani Sukma; Elly Malihah Setiadi; Wilodati Wilodati (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This study investigates the evolutionary and research trends on social capital and economic resilience within the small and medium enterprises sector through bibliometric analysis. Data were obtained from the google scholar through Publish or Perish software, covering the period from 2020 to 2025, then organized using Mendeley and analyzed through VOSviewer. The results indicate that topic of social capital is a central link between trust, innovation, and business sustainability. Research trends have shifted from theoretical approaches to practical applications, particularly during times of crisis or challenges. Overall, social capital is proven to be instrumental in strengthening the resilience and sustainability of SMEs, while also serving as the foundation for developing sustainable economic policies based on social capital.